2017
DOI: 10.3758/s13423-017-1302-z
|View full text |Cite
|
Sign up to set email alerts
|

Recognition-induced forgetting does not occur for temporally grouped objects unless they are semantically related

Abstract: Recent evidence has shown that practice recognizing certain objects hurts memories of objects from the same category, a phenomenon called recognition-induced forgetting. In all previous studies of this effect, the objects have been related by semantic category (e.g., instances of vases). However, the relationship between objects in many real-world visual situations stresses temporal grouping rather than semantic relations (e.g., a weapon and getaway car at a crime scene), and temporal grouping is thought to cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 42 publications
(56 reference statements)
2
20
1
Order By: Relevance
“…Memory for flanking objects (.53) was significantly worse than memory for baseline objects (.69, t(43)=5.72, p<.001, d=.77, scaled JZS 3 =17,889), and memory for target objects (.84) was significantly better than baseline (.69, t(43)=4.94, p<.001, d=.86, scaled JZS=1,624). 4 The significantly lower memory for flanking objects relative to baseline objects is the signature recognition-induced forgetting effect, replicating previous studies using this paradigm (Maxcey, 2016;Maxcey & Bostic, 2015;Maxcey et al, 2016;Maxcey et al, 2017;Maxcey & Woodman, 2014;Rugo et al, 2017). These results mimic the difference-of-Gaussian shape (Fig.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…Memory for flanking objects (.53) was significantly worse than memory for baseline objects (.69, t(43)=5.72, p<.001, d=.77, scaled JZS 3 =17,889), and memory for target objects (.84) was significantly better than baseline (.69, t(43)=4.94, p<.001, d=.86, scaled JZS=1,624). 4 The significantly lower memory for flanking objects relative to baseline objects is the signature recognition-induced forgetting effect, replicating previous studies using this paradigm (Maxcey, 2016;Maxcey & Bostic, 2015;Maxcey et al, 2016;Maxcey et al, 2017;Maxcey & Woodman, 2014;Rugo et al, 2017). These results mimic the difference-of-Gaussian shape (Fig.…”
Section: Resultssupporting
confidence: 78%
“…The stimulus set was larger to add more trials to the test phase, increasing task difficulty. Our previous studies using superordinate categories have shown very high accuracy and no forgetting (Maxcey et al, 2017). Although Experiment 3 here is different in a number of ways, we increased task difficulty to increase the likelihood of forgetting.…”
Section: Stimulimentioning
confidence: 96%
See 1 more Smart Citation
“…However, recent work has shown that pictures stored in long-term memory are susceptible to recognition-induced forgetting (Maxcey, 2016; Maxcey & Bostic, 2015; Maxcey, Bostic, & Maldonado, 2016; Maxcey, Glenn, & Stansberry, 2017; Maxcey & Woodman, 2014). Specifically, practice recognizing some objects held in long-term memory (e.g., a red vase) leads to the forgetting of semantically related objects also held in long-term memory but not accessed (e.g., a blue vase).…”
mentioning
confidence: 99%
“…Therefore it is hard to imagine how one would conduct a retrieval -induced forgetting study with faces. Second, recent evidence demonstrated that temporally grouped objects that belong to a scene (e.g., a cow and a tractor belong to a “farm” scene) do not suffer recognition-induced forgetting, suggesting that not all stimuli that can be semantically grouped together are susceptible to recognition-induced forgetting (Maxcey et al, 2017). Third, a long line of evidence demonstrates that long-term memory for pictures is fundamentally different than memory for words (Calkins, 1898; Durso & O’Sullivan, 1983; Gehring, Toglia, & Kimble, 1976; Hockley, 2008; Juola, Taylor, & Young, 1974; Kirkpatrick, 1894; Madigan, 1974; Münsterberg, 1894; Nelson, Reed, & McEvoy, 1977; Nelson, Reed, & Walling, 1976; Paivio & Csapo, 1973; Paivio, Rogers, & Smythe, 1968; Paivio, Yuille, & Madigan, 1968; Snodgrass & Burns, 1978; Snodgrass, Volvovitz, & Walfish, 1972; Snodgrass, Wasser, Finkelstein, & Goldberg, 1974).…”
mentioning
confidence: 99%